Identification and Implementation Strategy for Strengthening Bamboo Craft Industry in Papring Village, Banyuwangi - Ikhwanul Qiram; Muhajir (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
Papring Village - Kalipuro, is one of the eight main centers for bamboo handicrafts in Banyuwangi district. The purpose of this activity is to obtain a strategic study of strengthening the bamboo craft industry in the indigenous people of Papring Village. This activity is a pre-community service activity. The activity stages include field observations through interviews, field observations, FGDs and documentation. The data from the observations were then analyzed by SWOT to obtain supporting factors and inhibiting factors for business development. The results of the assessment show that 90% of the Papring community work as bamboo craftsmen. Abundant bamboo material is obtained from gardens and forests with five main species. The inhibiting factor for business development is the production process is still done manually with simple equipment. From the results of observations, the technology developed is in the form of technical production facilities and website-based E-commerce strategies. Production technology can have an impact on increasing production and product quality as well as as a means of product promotion in a wider market